2022
DOI: 10.3390/jof8040386
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Infection by Non-albicans Candida Species Affects the Development of a Murine Model of Multiple Sclerosis

Abstract: Candidiasis may affect the central nervous system (CNS), and although Candida albicans is predominant, non-albicans Candida species can also be associated with CNS infections. Some studies have suggested that Candida infections could increase the odds of multiple sclerosis (MS) development. In this context, we investigated whether systemic infection by non-albicans Candida species would affect, clinically or immunologically, the severity of experimental autoimmune encephalomyelitis (EAE), which is an animal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…It was unlikely to invade and damage host tissues similar to C. albicans due to its potential to protect the host from infection by C. albicans ( 50 , 51 ). Moreover, in an animal model of experimental autoimmune encephalomyelitis (EAE), it was reported that C. parapsilosis infection did not exacerbate the severity of EAE and exhibited the lowest fungal burden in the central nervous system ( 52 ). Furthermore, the yeast-hyphal morphogenesis is reported to be critical for fungal virulence ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was unlikely to invade and damage host tissues similar to C. albicans due to its potential to protect the host from infection by C. albicans ( 50 , 51 ). Moreover, in an animal model of experimental autoimmune encephalomyelitis (EAE), it was reported that C. parapsilosis infection did not exacerbate the severity of EAE and exhibited the lowest fungal burden in the central nervous system ( 52 ). Furthermore, the yeast-hyphal morphogenesis is reported to be critical for fungal virulence ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the mixture was centrifuged, and the supernatant was collected and placed in 96-well UV-transparent plates. The absorbance was measured at 280 nm [ 38 ]. The sap proteolytic activity was evaluated at 2, 4, 6, 8, 10 and 12 h.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were incubated for 1 h at 37 • C, and proteolytic activity was stopped by adding 5% trichloroacetic acid (TCA), followed by incubating for 1 h at 4 • C. Then, the mixture was centrifuged, and the supernatant was collected and placed in 96-well UV-transparent plates. The absorbance was measured at 280 nm [38]. The sap proteolytic activity was evaluated at 2, 4, 6, 8, 10 and 12 h.…”
Section: Evaluation Of Proteolytic Activity (Sap)mentioning
confidence: 99%
“…It reported that C. albicans infection before the induction of experimental autoimmune encephalomyelitis (EAE), the classic animal model of MS, promotes the EAE onset and aggravates the disease severity ( 57 ). In addition to C. albicans , EAE was also aggravated in mice infected with non- C. albicans strains C. glabrata and C. krusei ( 58 ), suggesting a critical role of fungi in promoting EAE disease progression.…”
Section: Fungi In Cns Autoimmune and Neurodegeneration Disordersmentioning
confidence: 99%